Hydrocarbons in sea water and coastal sediments of the Slovenian part of the Gulf of Trieste - Bajt, Oliver (Annales. Series historia naturalis, 2000)
In spite of the expected pollution of the marine environment of the Gulf of Trieste with hydrocarbons (heavy sea traffic, Ports of Koper, Trieste and Monfalcone), only a few data are available on the content of these compounds in sea water and sediment...
Keywords: Gulf of Trieste; morje; morski sediment; ogljikovodiki; onesnaževanje; pomorski transport; sea; spektrofluorimetrija; Tržaški zaliv